Efficacy of Nitrogen on Growth and Yield of Radish (Raphanus sativus L.) from Different Sources of Organic Manures - Pant, Krishna Raj; Oli, Biplov (International Journal of Applied Sciences and Biotechnology, 2021)
For the quantitative evaluation of the efficacy of Nitrogen through different plant nutrient sources in the growth and yield of radish, the field experiment was conducted from March 2020 to June 2020 in an Inceptisol with sandy loam soil of the research field of G. P. Koirala College of Agriculture and Research Centre, Gothgaun, Morang, Nepal. The experiment was carried out in a Randomized Complete Block Design with eight treatments (Biogas Byproduct, Poultry Manure, Goat Manure, Farmyard Manure, Vermicompost, Packaged Organic Manure, Recommended Dose of Chemical Fertilizer, and Control) and four replications. Forty Day (released in 1994 AD) variety of radish was used as a test crop. The recommended 100 kg N per hectare was supplied from each treatment, calculated based on the nitrogen content of each nutrient source. Results showed that there was a significant difference in almost all studied parameters from all treatments over control (P≤ 0.05). The highest total fresh biomass yield (123.415 Mt/ha) and highest delta fresh shoot yield (22.806 Mt/ha) were recorded from the application of a recommended dose of fertilizer, and the highest delta fresh root yield (30.127 Mt/ha) was obtained from the application of FYM. The experiment suggests that the application of FYM significantly increased root yield and was positively correlated with other parameters, which might be a good alternative for chemical fertilizers. Int. J. Appl. Sci. Biotechnol. Vol 9(3): 203-212.